1998
DOI: 10.1083/jcb.141.4.1019
|View full text |Cite
|
Sign up to set email alerts
|

The α5β1 Integrin Mediates Elimination of Amyloid-β Peptide and Protects Against Apoptosis

Abstract: The amyloid-β peptide (Aβ) can mediate cell attachment by binding to β1 integrins through an arg-his-asp sequence. We show here that the α5β1 integrin, a fibronectin receptor, is an efficient binder of Aβ, and mediates cell attachment to nonfibrillar Aβ. Cells engineered to express α5β1 internalized and degraded more added Aβ1-40 than did α5β1-negative control cells. Deposition of an insoluble Aβ1-40 matrix around the α5β1-expressing cells was reduced, and the cells showed less apoptosis than the control cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
67
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 56 publications
(66 reference statements)
5
67
2
Order By: Relevance
“…This sequence is also reported to be responsible for binding of Ab to a5b1 integrin. 47 Our results showing IF 1 -sensitive extracellular generation of ATP by the glioma C6 cell line lead us to the conclusion that in this cell type there must also be a competent F 1 F 0 -ATP synthase complex at the cell surface, which could also be shown for other cell types. [20][21][22]35 Another known inhibitor of ATP synthase subunit a activity is angiostatin, a proteolytically derived 38 kDa fragment of plasminogen.…”
Section: Discussionmentioning
confidence: 67%
“…This sequence is also reported to be responsible for binding of Ab to a5b1 integrin. 47 Our results showing IF 1 -sensitive extracellular generation of ATP by the glioma C6 cell line lead us to the conclusion that in this cell type there must also be a competent F 1 F 0 -ATP synthase complex at the cell surface, which could also be shown for other cell types. [20][21][22]35 Another known inhibitor of ATP synthase subunit a activity is angiostatin, a proteolytically derived 38 kDa fragment of plasminogen.…”
Section: Discussionmentioning
confidence: 67%
“…23 However, as it was shown for global hypoxia, 24 we can hypothesize that a5 integrin has been upregulated acutely after jTBI, and then returned to baseline after 2 and 6 months. Moreover, a5b1 integrin was previously shown to be involved in the clearance of Ab, 30 therefore the absence of increase of a5b1 integrin may also contribute to Ab accumulation observed in our model. To the best of our knowledge, the level of expression of a5b1 integrin after jTBI has never been studied before.…”
Section: Discussionmentioning
confidence: 85%
“…4 Interestingly, several other proteins have been proposed to participate in Ab clearance like other transporters (ABCA1 and ABCA2) 28,29 or like the receptor a5b1 integrin. 30 In addition, various basement membrane proteins, Figure 4. a5b1 integrin levels are not modified long term after a juvenile traumatic brain injury (jTBI).…”
Section: Discussionmentioning
confidence: 99%
“…Integrin subunits have been linked to the ability of cells to generate resistance to apoptosis (Faraldo et al, 1998 ;Matter et al, 1998 ;Rozzo et al, 1997 ;Scatena et al, 1998). We compared the ability of HaCaT-E6 cells to resist anchorage-independent induced apoptosis and found that HaCaT-E6 cells generate lower resistance to anchorage-independent induced apoptosis compared to HaCaT-Ras cells (data not shown).…”
mentioning
confidence: 99%